2015
DOI: 10.1108/jstpm-07-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

External factors influencing the readiness for implementing public-private partnerships among public and private organizations in Yemen

Abstract: Purpose – This paper aims to examine the external factors that influence the implementation of the new concept of public-private partnerships (PPPs) in Yemen. Design/methodology/approach – This study used a self-administered questionnaire that was distributed to Yemeni organizations. Data were analyzed using factor analysis, with appropriate tests of reliability, consistency, correlation and multiple regression analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Conclusion drawn from Medurii and Annamalai (2012) on evaluation of the level of private sector investment in road sector in developing countries indicated that states having lower levels of corruption could be more conducive for successful implementation of projects. Cruz and Marques (2012), Al-shareem et al (2015) and Ameyaw and Chan (2015) provided an insight into the skills and experiences of officials in the PSOs in relation to performance of PPP projects. Cruz and Marques (2012) evaluated the performance of PPP contracts by the local governments in the school sector based on four Portuguese case-studies.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusion drawn from Medurii and Annamalai (2012) on evaluation of the level of private sector investment in road sector in developing countries indicated that states having lower levels of corruption could be more conducive for successful implementation of projects. Cruz and Marques (2012), Al-shareem et al (2015) and Ameyaw and Chan (2015) provided an insight into the skills and experiences of officials in the PSOs in relation to performance of PPP projects. Cruz and Marques (2012) evaluated the performance of PPP contracts by the local governments in the school sector based on four Portuguese case-studies.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…The study concluded that increasing the transparency in procurement consequently improved project success. In Al-shareem et al (2015), engagement of external participants was considered an external factors influencing readiness for implementing PPP projects among PSOs in Yemen. The significance of the level of skills and experiences of officials in the PSOs in relation to performance of PPP projects was further justified by findings of Ameyaw and Chan (2015) that public officials in most PSOs would require additional training in the PPP procurement process in the water sector in Ghana.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…The Anglo-Saxon experiences of the United States, the United Kingdom, Australia, and Canada have attracted significant scholarly coverage (Pollitt, 2015). Recently, there has been growing contributions from continental Europe (Koppenjan, 2015; Teisman & Klijn, 2002), Scandinavia (Greve & Mörth, 2010; Petersen, 2010, 2011), Russia and Kazakhstan (Mouraviev & Kakabadse, 2015), China (Ke, Jefferies, Shrestha, & Jin, 2014), India (Vedachalam, Geddes, & Riha, 2015), Latin America (Vives, Benavides, & Paris, 2008), and the Middle East (Al-Shareem, Yusof, & Kamal, 2015; Jamali, 2004; Mistarihi, Hutchings, & Shacklock, 2013). However, Gulf Cooperation Council (GCC) states’ experiences have been overlooked in this literature (Biygautane, Hodge, & Gerber, 2016; Common, 2008; Pollitt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers, also, such as Ambler, Kokkinaki, and Puntoni (2004), identified several factors that are important to adopt innovation, including new technology, outsourcing, competition and the growing importance of service industries. In addition, Al-Shareem et al (2015) reported that adopting new ideas is driven by environmental forces. Authors further claimed that the advent of new technology has greatly motivated organizations to promote a quality standard.…”
Section: External Factor and Pms Adoptionmentioning
confidence: 99%